Multi-method analysis of a historic wooden trough from Kentucky, USA: a case study in corroborating artifact oral histories with heritage science - Katharine G. Napora; George M. Crothers; Carla S. Hadden; Lisa Guerre; Laura J. Waldman; Hugo Reyes-Centeno; James Keppeler; Madeline Imler; Edward Jakaitis; Alexander Metz; Philip B. Mink (Heritage Science, 2023)
Abstract Oral history indicates that a large wooden trough held in storage at the University of Kentucky’s William S. Webb Museum of Anthropology was a component of the saltpeter mining operation in Mammoth Cave in the late 18th and early 19th centuries, worked largely by enslaved persons. We used multiple heritage science methods, including radiocarbon wiggle-match dating, tree-ring dating, scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM–EDS), and optical scanning, combined with historical research, to examine the trough. Our analysis supports the oral history of the trough as an artifact of the mining system in Mammoth Cave. This case study illustrates how heritage science methods can provide corroboration for the origins and biographies of poorly documented historical artifacts.